Menganalisis Model Bisnis Usaha di Pentol Cw (Cak War) Lontar Dengan Business Model Canvas - Fatchur Rochman; Rina Dewi (Universitas 45 Surabaya, 2025)
This study aims to analyze the business model of Pentol CW MSMEs with a Business Model Canvas (BMC) approach and SWOT description. The data collection method uses observation, interviews, and documentation. The results show that Pentol CW has advantages in the mass customer segment, a value proposition based on unique flavors and affordable prices, as well as customer relationships that are built directly and personally. SWOT analysis shows that Pentol CW needs to improve operational efficiency and expand the market to increase competitiveness.This study aims to analyze the business model of Pentol CW MSMEs with a Business Model Canvas (BMC) approach and SWOT description. The data collection method uses observation, interviews, and documentation. The results show that Pentol CW has advantages in the mass customer segment, a value proposition based on unique flavors and affordable prices, as well as customer relationships that are built directly and personally. SWOT analysis shows that Pentol CW needs to improve operational efficiency and expand the market to increase competitiveness.